PoshPick / Aiman Ariff Suliman ... [et al.] - Suliman, Aiman Ariff; Ahmad Liza, Aina Aniqah; Anuar, Danish Faid; Mohd Rizal, Nur Alia Aqilah; Ibrahim, Nurin Farhah; Mohd Fabli, Siti Nur Nashwa Faqihah (2023)
PoshPick is an application that provides a service for people to shop online. Some personal shoppers were gathered in this application to facilitate customers when shopping online. We always strive to give the best service to our customers. This personal shopper application, PoshPick is a comprehensive platform designed to cater to the modern consumer's evolving needs in the retail landscape. Through a user-friendly interface and advanced algorithms, the application will provide tailored shopping recommendations, efficient navigation within stores, and seamless checkout experiences, all while integrating user preferences and real-time inventory data. In this New Product Development (NPD) report, we came out with a solution to this problem which is by developing a blueprint by using mobile applications. The product is considered as new to the firm – new product line to this organization. This mobile application will be used as the platform for the customers to shop their needs online. It will lead to easier and effective ways to buy their needs if they have no time or the store is located far away from their house. Our target market is workers, housewives, students, and rural residents who love shopping online. We want these targets to feel they are going through an easier way from the previous system. By proposing and developing the product, we hope we can ease the way of their current lifestyle.